Hedgehog pathway is involved in nitidine chloride induced inhibition of epithelial-mesenchymal transition and cancer stem cells-like properties in breast cancer cells. Issue 1 (December 2016) - Sun, Mingjuan; Zhang, Ning; Wang, Xiaolong; Li, Yaming; Qi, Wenwen; Zhang, Hanwen; Li, Zengjun; Yang, Qifeng
Abstract Background The complications of clinical metastatic disease are responsible for the majority of breast cancer related deaths, and fewer therapies substantially prolong survival. Nitidine chloride (NC), a natural polyphenolic compound, has been shown to exhibit potent anticancer effects in many cancer types, including breast cancer. The epithelial-mesenchymal transition (EMT) and the acquisition of cancer stem cells (CSCs)-like properties emerge as critical steps in the metastasis of human cancers. However, the effects of NC on the EMT and the CSCs-like properties in breast cancer cells, and the underlying molecular mechanisms are not fully understood. Results In the present study, MDA-MB-468 and MCF-7 cancer cells were treated with NC. Scratch and Transwell assays were performed to determine whether NC could attenuate the migratory and invasive capability of cancer cells; Mammosphere formation and flow cytometry analysis were performed to confirm that NC decreased CSCs-like phenotype; RT-PCR and western blot analysis were used to examine the expression level of EMT and CSC related markers in both cells. Mechanistically, NC could inhibit the components of Hedgehog pathway (smoothened, patched, Gli1 and Gli2), subsequently inhibited the expression of Snail, Slug and Zeb1, which were correlated with the significant changes of the expression of EMT related markers (N-cadherin, E-cadherin, and Vimentin) to reverse EMT. On the other hand, NC could also inhibit the expression of CSCs related factors such as Nanog, Nestin, Oct-4 and CD44 via Hedgehog pathway. Furthermore, transforming growth factor-β1 (TGF-β1)-induced increment of EMT and CSCs properties could be reversed by NC. Conclusions Taken together, these data indicated that NC suppressed breast cancer EMT and CSCs-like properties through inhibiting Hedgehog signaling pathway. Our study suggested that NC may be a potential anticancer agent for breast cancer.